On relativistic effects on electron transport in the banana regime in tokamaks - Marushchenko, I.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2019)
In the present work, the neoclassical transport theory in tokamaks is re-considered with the relativistic effects for electrons taken into account. Since such effects are important only in high-temperature plasmas, only the low collisional banana regime has been considered. The obtained formulations give a possibility to calculate the electron neoclassical fluxes in very broad range of temperatures.